2010
DOI: 10.5539/ijbm.v5n3p117
|View full text |Cite
|
Sign up to set email alerts
|

The Relationships between Technology and Different Teaching Role Attributes of Instructors in Malaysia

Abstract: The present study seeks to examine the influence of technology on these four roles. Two hundred and ninety two lecturers teaching in Malaysian tertiary educations were involved in this study. They were using different level of technologies for teaching. Questionnaires were used to solicit their responses which were distributed using various means; online, personal visits and regular mails. The measurement items were mainly adapted from Job Diagnostic Survey developed by Hackman and Oldham. The results from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
1
0
0
Order By: Relevance
“…The results of this study were in line with research conducted by Koehler et al (2011). The results of research by Juhdi et al (2010) revealed that teachers would have the ability to manage class (class management) if they often used technology.…”
Section: Effect Of Student Perceptions About the Lecturer Teaching Me...supporting
confidence: 87%
“…The results of this study were in line with research conducted by Koehler et al (2011). The results of research by Juhdi et al (2010) revealed that teachers would have the ability to manage class (class management) if they often used technology.…”
Section: Effect Of Student Perceptions About the Lecturer Teaching Me...supporting
confidence: 87%
“…; (Guava. V., Sing, W., 2019); (Hooper, D.T, Martin, R, 2019) ; ( Leo, Y., Zhang, C., 2020); ( Chen,2017) (Williamson, 2007); (Humphrey etal.,2007); (Juhdi etal.,2007); (Chen & Aryee, ,2005); (Liao & Rupp ,2005); (Liu,2004); (Grawitch & Barber, 2009 (Williamson, 2007); (Humphrey etal.,2007); (Juhdi etal.,2007); (Chen & Aryee, ,2005); (Liao & Rupp ,2005); (Liu,2004); (Grawitch & Barber, 2009) (Humphrey, et al, 2007), (Liu, 2004) , (Williamson, 2007) , (Juhdi et al, 2007) (Williamson, 2007); (Humphrey etal.,2007); (Juhdi etal.,2007); (Chen & Aryee, ,2005); (Liao & Rupp ,2005); (Liu,2004); (Grawitch & Barber, 2009)…”
mentioning
confidence: 99%